THYROID FUNCTION AND COGNITIVE DEVELOPMENT: A CROSS-SECTIONAL STUDY AT THE DEPARTMENT OF PEDIATRICS, LRH PESHAWAR - KHAN , I; AYESHA, .; MUHAMMAD , A (Biological and Clinical Sciences Research Journal, 2024)
Thyroid hormones play an essential role in brain development and cognitive function. Hypothyroidism can adversely affect children's mental development, leading to long-term developmental delays. Objective: This research aims to assess the correlation between thyroid hormones and child mental health, specifically examining the effects of changes in thyroid hormones on the cognitive outcomes of children receiving treatment at Lady Reading Hospital (LRH) Peshawar. Methods: A cross-sectional study was conducted in the Department of Pediatrics at LRH Peshawar from March 05, 2021, to September 05, 2021. One hundred children aged 2-8 years were randomly selected for the study. The mean age was 4.5 years, with a standard deviation of 1.3 years. Blood tests for TSH, T3, and T4 were performed to evaluate thyroid function. Cognitive development was assessed using standardised cognitive development tests appropriate for the children's ages. Descriptive statistics were used to analyse the data, and inferential statistics were employed to compare cognitive test scores between children with normal thyroid function and those with hypothyroidism, with a significance level set at p < 0.05. Results: The study found that thyroid function significantly impacts cognitive development. Children with normal thyroid hormone levels had better cognitive abilities compared to those with hypothyroidism. The mean cognitive test score for children with normal thyroid function was 85%, whereas children with hypothyroidism had a mean score of 65%. The p-value for this correlation was less than 0.05, indicating a statistically significant difference. Conclusion: Both hypothyroidism and hyperthyroidism significantly affect brain development in children. Early diagnosis and treatment of thyroid dysfunction are crucial to prevent developmental impacts. Incorporating thyroid function screening into routine health check-ups can enhance children's cognitive development.